The Effectiveness of Group Counseling with Role Playing Techniques Charged With the Value of Tapa Ngrame in the Panji Story to Increase Altruism in Elementary School Students: A Cultural Approach in Counseling - Abd. Hafid; Nur Hidayah; M. Ramli; IM Hambali (Kuras Institute, 2025)
This article aims to analyze the effectiveness of group counseling role playing techniques charged with the value of tapa ngrame in Panji stories to increase the altruism of elementary school students, which focuses on what the condition of elementary school students ' altruism looks like before and after treatment, analyzing the relationship between Panji stories and altruistic behavior. The design used in this study is an experimental design in the form of pretest and postetst control group design, the number of subjects in this study is 30 elementary school students in Bojonegoro Regency, where the groups set are not randomly selected (nonrandomly assigned group). The technique of data collection is done by using the scale of altruistic attitude insrtrumen amounting to 35 items. And data analysis techniques using independent sample t test and Pired samples test. The results of statistical tests using independent sample t test showed that there is a significant difference between the average value of pretest and posttes in the experimental group and the control group. This is indicated by a significance value of 0.000 or below 0.05. This means that there is a difference in the altrusitic attitude scores of students before being treated and after being treated, the results of this test are reinforced by the comparison of the results of the average posttest score in both groups. With the acquisition of scores for the experimental group of 104.46 and the control group of 89.93. And the results of the paired samples test showed an increase in the average score for the experimental group of 36.73 and for the control group of 22.4. This shows that the Counseling Group role playing techniques charged with the value of tapa ngrame in Panji's story are effective to improve the altruistic attitude of elementary school students.